Exploring the Impact of the COVID-19 Pandemic on Returnee Migrant Workers’ Income, Psychological Well-Being, and Daily Life Expenses: A Case Study in Thua Thien Hue Province - Thi Anh Tran, Nguyet; Le, Sen Thi Hoa; Bond, Jen; Mazancova, Jana; Hoang, Ha Dung; Nguyen, Dung Tien (Journal of Population and Social Studies [JPSS], 2024)
The COVID-19 pandemic has significantly affected the lives, economies, and cultures of communities in Vietnam despite it no longer being considered a global emergency. Migrant workers who returned to their localities during the outbreak are among the most vulnerable groups affected by the pandemic. This study surveyed 298 returning migrant workers in 6 Thua Thien Hue province coastal communes to understand the pandemic’s effects on them. Results indicate that the pandemic has affected migrant workers differently based on their work type, education level, and gender. The pandemic severely impacted workers’ employment and income, with self-employed workers being the most affected. The reduction in income led to changes in their quality of life, including cutting down on expenses and experiencing increased stress. In particular, female migrant workers with limited education have experienced heightened vulnerability and anxiety in comparison to their male counterparts, primarily attributed to their societal and caregiving responsibilities. However, most respondents intend to remigrate post-pandemic to continue sending remittances home regardless of the challenges ahead. The findings highlight the need for policies and support measures to improve the resilience and adaptive capacity of migrant workers in the post-pandemic period. These measures should focus on skill improvement, access to job placement networks, social insurance, and employment contracts, and raising awareness about the importance of saving income and providing psychological support.